UNJUK KERJA RICE TRANSPLANTER SISTEM JAJAR LEGOWO TIPE CROWN INDO JARWO DI KABUPATEN PINRANG SULAWESI SELATAN - Iqbal Salim; Yoesrifar Jafar; Tahir Sapsal (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
Rice transplanters have been used in Pinrang district since 2017. The machines are initially grant from the Government through the Ministry of Agriculture. The type of rice transplanters that is mostly found within farmer groups are the Crown Indo Jarwo type. This study aims to identify and determine the theoretical and field capacity of rice transplanter, as well as field efficiency of the machine. The method used in this research was field experimental and descriptive analysis. The research was conducted at three different speeds on 3 plots of rice fields with each size of 10 x 10 meters. The results showed that the rate of 1.52 km/hour was a good speed to use in paddy fields with a working capacity of 8.5 h/ha. The results obtained from the calculation of the theoretical field capacity were 0.14 ha/h or 7.14 h/ha. The effective field capacity was 0.12 ha/h or 8.33 h/ha with an efficiency of 86%. Keywords: field efficiency, rice, rice transplanter, work capacity